The Impact of the Presence of Military Barriers Artistically on Palestinian Novels (The International Journal for Scientific Research, 2024)
The article discusses the impact of the presence of military barriers artistically on Palestinian novels and their transformation, and the diversity of the novels that reflect reality and suffering, in addition to the role of language in expressing social conflicts and the challenges of reality, and the importance of reality as a source of characters and events in novels; military barriers are mirrors of the Palestinian reality. The article also addresses the militarization of vocabulary in the novel and its connection to the language of occupation, and touches on the use of satire and comedy in Palestinian novels and its implications, as literary satire helps liberate the human ability to sharp criticism. The article emphasizes that the new Palestinian novel is characterized by its realism and its choice of simple, precise language free of ornate embellishments and rhetorical adornments.
Keywords: Military Barriers; Palestinian Novels; Artistic Impact